Retrato de intimidad - Otaño, Estefanía (2023)
This article aims to analyze the stage incarnation of the Argentine monologue script Si te viera tu padre (If your Father Could See You) (2018) by Sofía López Fleming. In this monologue, whose creator is both the playwriter and actress embodying the text on stage, we study, with an analysis of the dramaturgical dimension linked to the scenic event (the encounter with the other), the textual, poetic, discursive, scenic, and performance procedures that express the incarnations of pain: how dramatic bodies speak, words touch the meaning and signify other bodies, generating an erotic and inter-subjective space between the scene and the audience. In this monologue, the female body is presented as a territory in which pain is imprinted. The embodied writing of this dramatic monologue configures a discursiveness that tenses the spectator’s space between I-you, appealing to the shock and resulting in the monologuing I, from intimacy, addressing the viewer, enabling an experience of shared pain, i.e. a collective experience of pain. It is in the embodiment that the dramaturgical practice gains power, testing ways of sharing loneliness, intimacy, pain in a public, convivial, ethical-aesthetic, and political act, and configuring a suffering-together, a community of mourners where to put in common our unique wounds and pains.